The role of leptin in nutrition and cancer - Gencoglu, Hasan; Şahin, Kazım (Nova Science Publishers, Inc., 2023)
Leptin is a hormone primarily secreted by adipose tissue that plays a crucial role in regulating energy homeostasis and feeding behavior. Understanding the role of leptin in cancer may provide insights into potential therapeutic targets for cancer treatment. Leptin signaling has been shown to promote cancer cell proliferation, angiogenesis, and invasiveness in several types of cancer, including breast, prostate, and colorectal cancer. Additionally, leptin has been shown to contribute to the resistance of cancer cells to chemotherapy and radiation therapy. However, the precise mechanisms underlying these effects of leptin on cancer development and progression are not yet fully understood. In addition to its well-known role in obesity and metabolic disorders, recent research has uncovered a potential link between leptin and cancer. This review summarizes the current understanding of the role of leptin in nutrition and cancer, focusing on its impact on cancer cell proliferation, angiogenesis, and immune response. Preclinical studies have demonstrated that inhibition of leptin signaling can suppress tumor growth and sensitize cancer cells to chemotherapy and radiation therapy. Clinical studies investigating the efficacy of targeting leptin signaling in cancer treatment are currently underway, and early results have shown promising results. Leptin signaling has been shown to activate various signaling pathways, including JAK/STAT, PI3K/Akt, and MAPK/ERK, which promote cancer cell growth and survival. Moreover, leptin can modulate the tumor microenvironment by promoting angiogenesis and inhibiting immune response, facilitating tumor progression. However, conflicting results exist regarding the association between leptin levels and human cancer risk. Thus, further research is needed to elucidate the complex interplay between leptin and cancer fully. In conclusion, the role of leptin in nutrition and cancer is an active area of research, and emerging evidence suggests that targeting leptin signaling may be a promising therapeutic strategy for cancer. Further studies are needed to elucidate the precise mechanisms underlying the effects of leptin on cancer development and progression and to determine the optimal therapeutic approach for targeting leptin signaling in cancer treatment. © 2024 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Cancer; Leptin; Molecular pathways; Nutrition